2016
DOI: 10.2139/ssrn.2737950
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hedging and Firm Performance: Evidence from Cross-Border Mergers and Acquisitions

Abstract: 2017) Financial hedging and firm performance: evidence from crossborder mergers and acquisitions. European Financial Management, 23 (3). pp. 415 458. AbstractThis paper studies the impact of financial hedging on firm performance in cross-border mergers and acquisitions (M&As). Using a sample of 1, 369 acquisitions announced by S&P 1500 firms between 2000 and 2014, we find strong evidence that derivatives users experience higher announcement returns than nonusers, which translates into a $193.7 million sharehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Existing studies have unveiled a posi-tive relation between derivatives hedging and firm performance (see Bartram et al, 2011;Haushalter et al, 2007;Pérez-González and Yun, 2013). More recently, Chen, Han and Zeng (2017) also provide robust evidence in support of the view that companies who use derivative hedging achieve higher returns than non-users do.…”
Section: Managerial Implications Of Liq-garch Modelmentioning
confidence: 82%
See 1 more Smart Citation
“…Existing studies have unveiled a posi-tive relation between derivatives hedging and firm performance (see Bartram et al, 2011;Haushalter et al, 2007;Pérez-González and Yun, 2013). More recently, Chen, Han and Zeng (2017) also provide robust evidence in support of the view that companies who use derivative hedging achieve higher returns than non-users do.…”
Section: Managerial Implications Of Liq-garch Modelmentioning
confidence: 82%
“…Several studies have shown that there exists a positive relationship between derivatives hedging and firm performance (see Allayannis et al, 2012;Bartram, Brown and Conrad, 2011;Haushalter et al, 2007;Pérez-González and Yun, 2013). More recently, Lau (2016) has shown that hedging can strengthen company's ROA and ROE, while Chen, Han and Zeng (2017) find that hedging companies announce higher returns than non-users. Typically, hedging strategies are supported by a variety of econometric models aiming at forecasting the volatility of commodity prices.…”
Section: Financial Hedging and Business Performance: A Reviewmentioning
confidence: 99%